Semiotics, semiology and film - Keyan Tomaselli (Communicare)
Semiotics and semiology are quite different paradigms stemming from different origins. This paper demonstrates the differences and developes C.S. Peirce's notions of Phaneroscopy, Firstness, Secondness and Thirdness, explores his notion of Interpretants and applies these to the study of film. Peirce's theory is shown to be much more adaptable than the semiology developed by Metz from de Saussure's linguistic con- cepts. Whereas Metz's theory of signs can only take account of narrative cinema, the extention of Peirce's theory proposed here is able to account for all types of cinema from narrative to abstract.